Diotima at the barricades French feminists read Plato - Miller, Paul Allen 1959- (Classics in theory, 2016)
'Diotima at the Barricades' argues that the debates that emerged from the burgeoning of feminist intellectual life in post-modern France involved complex, structured, and reciprocal exchanges on the interpretation and position of Plato and other ancient texts in the western philosophical and literary tradition